PENERAPAN METODE CURAH IDE DAN MEDIA FOTO (CUDENFO) UNTUK MENINGKATKAN HASIL BELAJAR MENULIS PUISI PADA SISWA X IPS-3 SEMESTER 2 SMA NEGERI 1 KAMAL TAHUN PELAJARAN 2018/2019 - Sri Rukiyati Ningsih (Jurnal Sastra Aksara, 2020)
This research is a classroom action research, research that tries to apply a method and learning media to improve student learning outcomes. The method and media applied in this study are the method of brainstorming ideas and photo media or abbreviated as Cudenfo. The problems examined in this study are the steps/ways of implementing learning by the Cudenfo method and increasing students' ability to write poetry through the Cudenfo method. In line with the formulation of the research problem, the purpose of this study is to describe the application of the Cudenfo method and media in learning to write poetry and to measure the improvement in learning outcomes of writing poetry in class X IPS-3 students learning to write poetry with the Cudenfo method and media. In the first cycle, teachers still use much of the lecture time because students do not understand well the tasks they have to do. In the first cycle, the teacher uses 40 minutes to explain the steps and give examples of how to do the task. In the first cycle, the average value obtained was 67 with enough predicate. In the second cycle, the dominant activity is student activity. In this second cycle student learning outcomes increase. The achievement of the average value of students in this cycle is 75 with a good predicate. By comparing student learning outcomes in cycles I and II it can be said that the application of the brainstorming method and photo media (cudenfo) can improve student learning outcomes in writing poetry.